Pengaruh Pembelajaran CTL Melalui Media Handout Terhadap Hasil Belajar Siswa Kelas VIII pada Materi Sistem Pernapasan Manusia - Siti Sholikatin Ni’mah; Hernik Pujiastutik (Universitas Sebelas Maret, 2018)
Education in Indonesia still focuses on teachers as the main source of knowledge, then lectures become the main choice of teaching and learning strategies.Improving the quality of education can be implemented through various models and learning media.One of the model and learning media that can be used is CTL learning model (Contextual Teaching Learning) by using handout media.The learning model of CTL using handout media is one of the efforts that can be used to improve student learning outcomes.Through the learning model of CTL and the media of this handout learners can directly know the important points by linking the material in real life so as to make the students become more active and attract the attention of students in following the learning process. Then do research about learning of CTL through media handout with aim to know influence of learning of CTL through media handout to result of student study of class VIII MTs Salafiyah Kerek on material of human respiration system. Research conducted in MTs Salafiyah Kerek.The population in this research is all students of class VIII MTs Salafiyah Kerek.The sample in this research is only taken 2 class that is class VIII C (experiment) and class VIII D (control) which amounted 22 x 2 = 44 students.Parameters in this study in the form of data on student learning outcomes in the analysis by using SPSS program 19. The results showed that the average score of student learning outcomes that followed the learning of CTL through the media handout in the experimental class of 81.82 and the average score of student learning outcomes that follow the conventional learning in the control class of 77.04. So, it can be concluded that the learning outcomes of students who follow the learning of CTL through the media handout better than students who follow the conventional learning